LIBYA AND THE ARAB WORLD: A GEOGRAPHICAL VIEW - Blake , Dr Gerald H. (مجلة كلية الاداب, 1972)
« The Arab World » is a term used very widely both in the West and in countries of the Middle East and North Africa, but what precisely is meant by it? Can it be: defined and drawn on a map? If so, is the concept of an Is the Arab World valid? There is of course no simple answer to these questions, but a number of answers might be suggested. Historically, the Arab World comprised those vast areas of South West Asia, North Africa and Southern Europe which fell to Islam during the seventh and eighth centuries. The early impetus for these amazing conquests came from Arabs from the Arabian peninsula, most of them nomadic tribesmen from central Arabia. To begin with little or no attempt was made to convert conquered peoples to Islam, but where conversion occurred voluntarily as was frequently the case, the defeated races automatically became the equals of the conquerors and were able to mix and intermarry with the Arabs. In time therefore the terms « Moslem » and « Arab > became virtually synonymous, and by the middle of the eighth century AD. conquests in the name of Islam were being conducted by others, and the flow of warriors, administrators and migrants from Arabia became less important. In 75C A.O. (133 A.H.) the Abbasid dynasty seized power, and with its capital in Baghdad the empire became essentially Islamic rather than Arab and multi-racial. Nevertheless, through the ninth and tenth centuries, A.D ., Arab culture became more firmly established and en